IMPLEMENTATION OF PROJECT CITIZEN MODEL BASED ON CHARACTER EDUCATION TO IMPROVE THE CRITICAL THINKING SKILLS - Eka Aprilya Handayani; Asti Sugiarti Sonodihardjo; Asmawati Asmawati (Universitas Negeri Makassar, 2020)
This study aims to determine the increase in students' critical thinking skills through the implementation of a citizen education model based on character education. The method used is a Classroom Action Research (CAR) which includes planning, action, observation, and reflection. The subjects of this study were students of PoliteknikPertanianNegeriPangkajeneKepulauan32nd 2019 in the Agro-Industry Study Program. Data collection was performed using test and non-test techniques. The form of data analysis uses qualitative analysis. It can be concluded that the implementation of learning with the project citizen model succeeded in increasing students' critical thinking skills in MKWU learning. This is evidenced by the increase in the average percentage of critical thinking skills in both cycles. Increased students' critical thinking skills occur because the project citizen model is based on the process of involving students in identifying real problems that originate from the surrounding environment so as to stimulate the ability to reason and think reflective which is focused on deciding the things that are believed and done. In addition, indicators interact with ethics and polite language as a component of character education also increased.